The social component of teaching in multicultural schools - students’ perspective - Car, Sandra; Kolak, Ante; Markić, Ivan, pedagog (2014)
This paper focuses on the issue of the teaching process in multicultural school environment with an emphasis on the social component from the perspective of students. Teaching as an organized process of active partnership and acquisition of knowledge is the most systematic and the most organized way of educational process. It is based on the principles of cultural pluralism and implies mutual understanding, tolerance and dialogue, experience and penetration of different cultural features.Given the width and breadth of the definition of teaching, the theoretical and the empirical part of the paper are focused on the study of the social aspects of teachingexclusively. Above mentioned aspect is determined and operationalized through the personalitydevelopment, development of peer relations, development of tolerance, non-violent conflict resolution procedures, the feeling of success, developing positive cooperative relationships, student satisfaction, creativity, value of respect and intercultural communication. The paper is a part of the scientific project Curriculum of social competences and relationships in school.
Projekt MZOS
ENG